Sensing system for salinity testing using laser-induced graphene sensors - Nag, Anindya; Mukhopadhyay, Subhas Chandra; Kosel, Jürgen (Sensors and actuators. A. Physical., 2017)
•A low-cost salinity system was developed and implemented.•Laser ablated graphene was formed from commercial polyimide films.•The photo-thermally induced graphene was transferred to Kapton tapes to form sensor patches.•Salt samples with different concentrations were tested with these sensor patches via serial dilution.•A microcontroller based system was formed to enhance the signal conditioning circuit. The paper presents the development and implementation of a low-cost salinity sensing system. Commercial polymer films were laser ablated at specific conditions to form graphene-based sensors on flexible Kapton substrates. Sodium chloride was considered as the primary constituent for testing due to its prominent presence in water bodies. The sensor was characterized by testing different concentrations of sodium chloride. A standard curve was developed to perform real-time testing with a sample taken from sea water of unknown concentration. The sensitivity and resolution of these graphene sensors for the experimental solutions were 1.07Ω/ppm and 1ppm respectively. The developed system was validated by testing it with a real sample and cross checking it on the calibration curve. The signal conditioning circuit was further enhanced by embedding a microcontroller to the designed system. The obtained results did provide a platform for implementation of a low-cost salinity sensing system that could be used in marine applications.